The contribution of social comparison to quarter life crisis in final year students at Padang State University - Vahmi, Nurul Intan; Elrisfa Magistarina (Causalita, 2025)
The crisis phenomenon that often occurs among students especially final year students, is the background for this research. The aim of this research is to find out how the contribution of social comparison can influence the level of quarter life crisis in final year students at Padang State University. This study collected 131 subjects. To obtain data, the scale by Hombing & Simarmata (2023) was used to measure the quarter life crisis. Adapting the INCOM scale by Gibbons & Buunk (1999) was carried out to measure social comparisons made by individuals. This study carried out simple linear regression data analysis with the help of the SPSS 24 computer program. The research results showed that social comparison had a positive contribution to the quarter life crisis of 35.1%, meaning that social comparison was able to improve the quarter life crisis in individual final students. This means that it is important for final year students to be able to understand the mechanism by which a crisis arises and how social comparison is able to increase or reduce the crisis situation in order to help individuals manage the crisis they are facing.